Dispute resolution in the field of intellectual property law in Uzbekistan (TSUL LEGAL REPORT, 2026)
This article discusses ongoing reforms in the field of intellectual property protection in Uzbekistan. In particular, the issues of administrative responsibility for violation of intellectual property rights, the process of judicial protection are covered. Opinions were also expressed on the procedure for resolving disputes in the field of intellectual property by administrative, civil and criminal courts. At the same time, based on the types of intellectual property objects (industrial property objects, means of individualization, copyright), the features of resolving conflict situations related to them are revealed. Based on the results of the article, the author concluded that it is necessary to specialize courts in resolving disputes in the field of intellectual property, expand the mechanisms of alternative ways of resolving disputes in the field of intellectual property, and improve the system of enforcement of judgments on intellectual property.